2011
DOI: 10.1111/j.1469-8749.2010.03876.x
|View full text |Cite
|
Sign up to set email alerts
|

Does physiotherapeutic intervention affect motor outcome in high-risk infants? An approach combining a randomized controlled trial and process evaluation

Abstract: AIM The aim of this study was to examine the effects of intervention in infants at risk of developmental disorders on motor outcome, as measured by the Infant Motor Profile (IMP) and using the combined approach of a randomized controlled trial and process evaluation.METHOD At a corrected age of 3 months, 46 infants (20 males, 26 females) recruited from the neonatal intensive care unit at the University Medical Centre Groningen (median birthweight 1210g, range 585-4750g; median gestational age 30wks, range 25-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(117 citation statements)
references
References 29 publications
(33 reference statements)
3
108
0
6
Order By: Relevance
“…Further studies will have to explore these associations to an extent that can inform about causality. Our findings were in accordance with the findings of Hielkema et al, 24 who also found positive correlations between physical therapy actions characteristic for COPCA and developmental outcome at 18 months CA measured with the IMP. The findings perhaps are related to the COPCA approach, which aims at supporting family members on the basis of an ongoing, equal partnership in order to uncover their own specific problemsolving strategies for caring and coping with the infant with special needs.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Further studies will have to explore these associations to an extent that can inform about causality. Our findings were in accordance with the findings of Hielkema et al, 24 who also found positive correlations between physical therapy actions characteristic for COPCA and developmental outcome at 18 months CA measured with the IMP. The findings perhaps are related to the COPCA approach, which aims at supporting family members on the basis of an ongoing, equal partnership in order to uncover their own specific problemsolving strategies for caring and coping with the infant with special needs.…”
supporting
confidence: 93%
“…Apart from the primary outcome, the IMP, 24 At 18 months CA, a neurological assessment was carried out according to Hempel. 39 The findings of the Hempel assessment were classified as neurologically normal, simple MND, complex MND, or CP.…”
Section: Developmental Outcomementioning
confidence: 99%
“…No early intervention programme has yet demonstrated a long-lasting effect on motor development, in either preterm children (Spittle et al, 2012) or children at high risk of developmental disorders (Hielkema et al, 2011). As suggested by Hadders-Algra (2011), this might be because the previous programmes apply a broad developmental perspective and include various more or less defined treatment elements administrated to a heterogeneous group of children, i.e., including children who would not later fulfill the diagnostic criteria of CP (Hadders-Algra, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Using a variety of strategies that fostered the infants' selfmotivated, independently produced motor activities, these improved developmental outcomes included functional mobility. Hielkema et al (2011) During this time in children's lives, it is important for their families to receive an understanding of O&M to help them support the foundational skills necessary to establish good habits and to build more advanced travel skills in the future (Beelmann & Brambring, 1998;Kesiktas, 2009). O&M training for young children (birth through 3 years old) with B/VI involves a team-based, familycentred approach that focuses on sensory, concept, and movement development (Joffee, 1988;.…”
Section: The Need For Oandm In Early Interventionmentioning
confidence: 99%